Young Chinese consumer decision making in buying green products: An application of theory of planned behavior with gender and price transparency - Muhammad Yaseen Bhutto; Fue Zeng; Yasir Ali Soomro; Mussadiq Ali Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
As environmental awareness increases, consumers tend to focus more on environmental friendly products. The literature on green consumption has recently focused on the Asian markets, in particular, the populous country of the world 'china'. Despite many efforts by the marketers to promote the environmental awareness among Chinese consumers and their buying behavior towards the green products are not yet completely understood. This paper examines the green purchase behavior of Chinese consumers using theory of planned behavior. In this attempt, a conceptual model is developed to study the effects of the standard 'theory of planned behavior' predictors; attitudes, subjective norms and perceived behavioral control (PBC) on green buying behavior. In addition, the role of gender and price transparency in the relationship between green purchase intention and behavior are also examined. Surveys were collected from 370 young full-time students; structural equation modeling (SEM) has been used to analyze the data. The result showed a significant correlation among between the attitudes, subjective norms, perceived behavioral control (PBC), green purchase intention (GPI), and green purchase behavior (GPB). Thisempirical study contributed to the current state of knowledge by showing that gender also plays a role in the purchase intention, and price transparency also has a moderate influence. The study concluded with a discussion of the results and provided theoretical, administrative, and research implications for giving awareness of the green products in China.
Keywords: 330; buying green products; theory of planned behavior; young consumers; price transparency; green purchase intention; green purchase behavior; subject norms; pro-environmental behavior